Unification of Mixing and Cellular Metabolism in Bioreactor Modeling: A Multi-scale Approach - Liew, Emily; Nandong, Jobrun; Samyudia, Yudi (RSCE-SOMCHE 2008, 2008)
In this paper, we address the progress, challenges and prospect of modeling of mixing in bioreactor. We aim to briefly review the progress in the integration of the mixing behaviors into bioreactor modeling and simulation as well as the obstacles faced towards this integrative modeling effort. Efficient operation of bioreactor is crucial in the biotechnological process, not only to ensure good yield but also to maintain the consistent product quality. Process modeling technique has frequently been adopted in the bioreactor design, optimization and control as well as in scale-up process. Transport phenomena problems have generally posed challenging tasks in the bioreactor scale-up. In this respect, the integration of mixing phenomena into the bioreactor modeling is considered as a vital aspect in the design and scale-up of bioreactor.